Click chemistry-based enrichment strategy for tracing cellular fatty acid metabolism by LC-MS/MS - Ru-Jie Yang; Jian Zou; Jia-Yue Liu; Jiang-Kun Dai; Jian-Bo Wan (Elsevier, 2023)
Fatty acids (FAs), which were initially recognized as energy sources and essential building blocks of biomembranes, serve as the precursors of important signaling molecules. Tracing FA metabolism is essential to understanding the biochemical activity and role of FAs in physiological and pathological events. Inspired by the advances in click chemistry for protein enrichment, we herein established a click chemistry-based enrichment (CCBE) strategy for tracing the cellular metabolism of eicosapentaenoic acid (EPA, 20:5 n-3) in neural cells. Terminal alkyne-labeled EPA (EPAA) used as a surrogate was incubated with N2a, mouse neuroblastoma cells, and alkyne-labeled metabolites (ALMs) were selectively captured by an azide-modified resin via a Cu(I)-catalyzed azide-alkyne cycloaddition reaction for enrichment. After removing unlabeled metabolites, ALMs containing a triazole moiety were cleaved from solid-phase resins and subjected to liquid chromatography mass spectrometry (LC-MS) analysis. The proposed CCBE strategy is highly selective for capturing and enriching alkyne-labeled metabolites from the complicated matrices. In addition, this method can overcome current detection limits by enhancing MS sensitivity of targets, improving the chromatographic separation of sn-position glycerophospholipid regioisomers, facilitating structural characterization of ALMs by a specific MS/MS fragmentation signature, and providing versatile fluorescence detection of ALMs for cellular distribution. This CCBE strategy might be expanded to trace the metabolism of other FAs, small molecules, or drugs.